Անբարեխիղճ մրցակցությունը և Հայաստանում դրա կարգավորման մարտահրավերները - Միքայելյան, Միքայել (Bulletin of Yerevan University G: Economics, 2017)
The development of the Armenian economy is impossible without effective protection of economic competition. Unfair competition is one of the most common manifestations hampering competition in our country. The article presents the essence of the concept of unfair competition, the forms of its manifestation, the challenges of its regulation in Armenia and their solutions.
Keywords: unfair competition, competition protection, misleading ihe society, abuse, sanctions